A Review of Perceptions of Classical Armenia: Romano-Parthian Relations - Yaser Malekzadeh; Sorour Khorashadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book of Perceptions of Classical Armenia: Romano-Parthian Relations, 70 BC-AD 220 is a Persian translation of a master thesis at Louisiana State University: Perceptions of Classical Armenia: Romano-Parthian Relations, 70 BC-AD 22. This research has mainly focused on the military actions of the Roman emperors from 70 BC to 200 AD. By comparing the various views on the foreign policy of the Romans in the Eastern regions, the political controversy, and especially the conflict between the Romans and the Parthians during these periods, it was aimed to show the image of the Parthians that Romans had in their mind. This article is a review of the research. A comparative study is conducted between the original English version of the book and its Persian translation to examine the accuracy of the content of the work and the translation. Having in mind that there are several well-known works on this subject that have been published in the West. Translating a mediocre work by a translator with a poor command of English language does not seem beneficial. Therefore, it would be more suitable to select another book and/or translator for this subject.